Can scientists remain internationally visible after the return to their home country? A study of Chinese scientists - Ying Zhang; Cornelia Lawson; Liangping Ding (The University of Manchester, The Manchester Institute of Innovation Research (MIoIR), 2023)
Returning scientists play a critical role in building up the academic workforce and science in their home country. Yet, in this study we argue that return mobility may limit scientists‟ international relevance and thus spillover effects may not be realised. We take scientists returning to China as a sample to investigate the impact of return mobility on international visibility/impact. What is more, we explore the roles of the international collaboration network and international knowledge base in this effect. Our findings clarify the limitation of return mobility and provide some empirical evidence on the limits of global knowledge spillovers in science and talent introduction policies.
Keywords: 330; International mobility; International collaboration; Academic performance; Research visibility; Knowledge spillovers